Pengaruh Solvabilitas dan Profitabilitas terhadap Audit Delay dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Dika Candra Laili; IBK Bayangkara (Pusat Riset dan Inovasi Nasional, 2025)
His study aims to examine the effect of profitability and solvency on audit delay and company size as a moderating variable. Audit delay is a condition where a company experiences a delay in issuing audited financial statements so that this condition can affect the quality of financial statement information. The populationlin this study were banking sector companies listed on the Indonesia Stock Exchange in 2019-2021. This study used a purposive sampling method. The sample in this study consisted of 30 companies using a purposive sampling technique.The data analysis techniques used were descriptive statistics, classical assumption tests, and hypothesis.testing using multiple linear regression analysis. The independent variable in this study is audit delay. The dependent variables in this study are Profitability and Solvency. The moderating variable in this study is Company Size. The research data are in the form of annual financial reports obtained from the official website www.idx.co.id andlthe official website of the related company. The data analysis method used is moderated regression analysis (Moderated Regression Analysis) with the SPSS application.